(untitled) (Medico Legal Update, 2021)
Background: Infertility is a case assuming approximately 15 percent of couples in the world. At Italy, the evaluated percentage increases to 20 percent. There are many reasons for this case, among that a significant function appears to be manipulated by infections of the genital tract. Aim of the Study: For assessments the influence of syphilis on the safety of infertile patients. Materials and Method: All specimens of serum were initial evaluated utilizing a non–Treponema pallidum serologic(Ag) analysis to estimated for syphilis disease, & then a Treponema pallidum serologic (Ag) analysis was proceed to assert the positive specimen of syphilis recognized via the checking test. Results: a total of 137 cases of infertile patients were collected (83 cases in male, 54 cases in female), from 83 cases of infertile male founded that 20 cases were suspected to T. pallidum infection while from 54 case of infertile female were founded that 15 cases were suspected to infection with Treponema pallidum bacteria. Also these results show that patients with continuous infertility have significant level of T. pallidumin females with age 41-50 years (54.55) while males with age 31- 40 years (34.62) than the age suspected for T. pallidum is > or = 41 years. Conclusions: A positive date of syphilis contagion may decrease the average of clinical gestation by sexual contact. Also, this decreasing in the average of clinical gestation needs a diversity of agents, including density of endometrial, grown oocytes number, the number of pollinated, splited oocytes under normal conditions, & the average of implantation.